Strategi Kepala Madrasah dalam Mengembangkan Kegiatan Ekstrakurikuler di MA Ma’arif Al Muhtadi Sendangagung Paciran Lamongan - Hidayatul Mufidah; M. Fathor Rohman; Arina Thoriqotul Firdaus (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
The development of extracurricular activities is important to do, because intracurricular activities are still lacking in developing the potential of students. So it is necessary to have companion activities that can help maximize the potential of students. This study aims to answer several problem formulations, namely, the strategy of the head of the madrasa in developing extracurricular activities, the supporting and inhibiting factors of the principal in developing extracurricular activities. In order to find out the problem and get accurate data, the researcher used observation, interview and documentation methods and used qualitative descriptive analysis techniques. The results of this study, that the principal's strategy in developing extracurricular activities at this madrasa are 1). by dividing into 2 parts in charge, namely PK IPNU IPPNU and Scouts; 2) by involving all stakeholders, especially waka students and coaches to participate in developing extracurricular activities; 3) guided by the vision and mission of the madrasa which reads "High Faith, Superior Achievement, Praiseworthy Morals, Skilled in Innovating (Strong)"; 4) the head of the madrasah appoints a BP teacher to assess the strengths and weaknesses of the students and their extracurricular activities. In addition, it also goes through several stages: a) needs analysis which also aims to identify the needs, potentials, and interests of students; b) determine the type of extracurricular activities through tests, questionnaires, and interviews; c) develop a program of extracurricular activities; d) the implementation stage, namely the implementation of extracurricular activities carried out according to the schedule made by each organization, as well as the implementation of obligatory and non-mandatory activities; e) monitoring and evaluation stage. And as for the supporting factors in developing extracurricular activities, among other stakeholders having the same vision, the existence of breakthrough ideas and good innovations from the head of the madrasa, the management of the IPNU IPPNU PK organization and active Scouts, adequate facilities and infrastructure. Meanwhile, the inhibiting factors for the head of the madrasa in developing extracurricular activities after conducting interviews were as described above, as follows: Lack of funds to support activities, less active students in carrying out activities, less active trainers in training students, the rise of the Covid-19 outbreak until implementation of the PPKM. As for the results of the study, it is suggested that in the future the head of madrasah should be more alert in dealing with existing problems and must be able to motivate students to be more active in carrying out the programs that have been made.